Cardio-ankle vascular index- а new cardiovascular risk predictor - I. V. Milyagina; V. A. Milyagin; Yu. M. Pozdnyakov; Yu. N. Leksina; V. V. Kopteva (Кардиоваскулярная терапия и профилактика)
Aim. To demonstrate the independence of cardio-ankle vascular index (CAVI) from blood pressure (BP) level, to investigate CAVI associations with various risk factors (RFs) of cardiovascular disease (CVD), to determine prognostic CAVI level.Material and methods. In total, 1563 individuals were examined: 447 healthy subjects, 855 patients with arterial hypertension (AH) and 261 patients with diabetes mellitus (DM). BP level, CAVI and brachio-ankle pulse wave velocity (PWV) were measured by volume sphygmography method (VaSera-1000, "Fukuda Denshi", Japan).Results. Volume sphygmography method demonstrated high reproducibility, with CAVI independence from BP level. CAVI was dependent on CVD RFs: age, AH, DM, family history of AH, overweight, waist circumference, and hypercholesterolemia. Vascular wall stiffness could integrate CVD RF influence on the organism, which is reflected by CAVI. Prognostic CAVI level was equal to 9.Conclusion. Volume sphygmography method, with CAVI assessment, could be used in the screening for people with high CVD risk.